Il significato dei colori in Le Bonheur (Materiali di Estetica. Terza serie, 2023)
The article is dedicated to the analysis of Varda’s work, Le Bonheur (1965). The montage, seemingly totally unrelated to the plot, is a demonstration of how much Varda’s work speaks in symbols: in a film in colour, the colours themselves are the best symbols available for the creation of a narrative parallel to that of the facts, a narrative that is at times autonomous and so coherent that it can even be traced in sequences not directly shown by the director.
Keywords: Agnés Varda; Cinema; Colours